The search for truth - Bausola, Adriano (Medicina e Morale, 1993)
Today there is a widespread belief that it is impossible to reach absolute metaphysical truths. The consequence of this conviction is that it is a Iso impossible to reach objective truth in the field of ethics. The article shows the connections of this beliefs with nihilism, both extreme (Nietzsche) and moderate, and it aims to show that such nihilism is impossible in fact and by right.